Improving quality of life and end of life care for people with dementia using the soundtrack to my life tool: evaluation report, University of Nottingham - Argyle, Elaine; Kelly, Tony (University of Nottingham, 2014)
Good support at home for people with dementia and their carers is crucial to maintaining their quality of life and helping them to remain in their own home. Person centred packages of care have been shown to be an effective means of providing this support. In this pilot study we aimed to improve quality of life of people living with dementia at (including at end of life) and their carers. This would be by using and evaluating, a bespoke, person centred music tool: Soundtrack to My Life (STML) with a dementia specialist home care team supporting people with dementia in their own homes. The STML tool is designed to draw together pieces of music representing significance in the life of a person with dementia, as part of a bespoke life history /biographical care plan. In using the tool, it was hoped that engagement of people with dementia by support staff would improve and that support staff would be encouraged to reflect on their practice, enhancing their interpersonal skills. The research phase of the project aimed to evaluate the way that using such a personalised compilation of music contributed towards improving quality of life. The evaluation used a questionnaire and semi-structured interviews to seek feedback from care workers and key managers about the degree to which the tool had benefitted the person with dementia and their principal carer.